Farm advisors amid the transition to Agriculture 4.0: Professional identity, conceptions of the future and future‐specific competencies. Issue 2 (26th January 2022) - Charatsari, Chrysanthi; Lioutas, Evagelos D.; Papadaki‐Klavdianou, Afroditi; Michailidis, Anastasios; Partalidou, Maria
Abstract: The transition to Agriculture 4.0 creates new responsibilities for farm advisors and initiates changes to the professional trajectories. In this work, following a mixed research design, we examine how Greek advisors experience the transition to and anticipate the future of Agriculture 4.0. We also aim at identifying what elements they are changing in their professional identities to respond to the challenges associated with Agriculture 4.0, which are the new responsibility‐related competency needs that this transition generates, and how conceptions of the future of farming impact upon these needs. Our findings suggest that the transition to Agriculture 4.0 urges the emergence of a new culture, in which data and technology are considered more reliable than human advice, and creates new responsibility gaps. To cope with these changes, advisors add new roles in their professional identities, emphasising the principle of beneficence and paying limited attention to the societal externalities of transition. Advisors view Agriculture 4.0 as a threat or disruption more than as evolution or promise. In parallel, they prioritise different sets of competencies needed to responsibly facilitate agricultural digitalisation, depending on how they grasp the future of Agriculture 4.0.